2003
DOI: 10.1002/anie.200351167
|View full text |Cite
|
Sign up to set email alerts
|

Magic Ring Rotaxanes by Olefin Metathesis

Abstract: Trick or treat? Ruthenium alkylidene catalyzed ring‐closing metathesis of crown ether like diene substrates around a dumbbell‐shaped secondary ammonium ion affords [2]rotaxanes. The reversible nature of this process has been demonstrated through a “magic ring” synthesis, wherein the preformed olefinic macrocycle and dumbbell‐shaped component equilibrate to form the hydrogen‐bond‐stabilized [2]rotaxane in the presence of a metathesis catalyst (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…4 In the glovebox, sodium hydride (95%, 288 mg, 12 mmol) was added to a 20 mL scintillation vial equipped with a stirbar. The vial was sealed with a pierceable Teflon-lined septum cap and brought out of the glovebox.…”
Section: Synthesis Of C 6 Eo 4 π Monomermentioning
confidence: 99%
“…4 In the glovebox, sodium hydride (95%, 288 mg, 12 mmol) was added to a 20 mL scintillation vial equipped with a stirbar. The vial was sealed with a pierceable Teflon-lined septum cap and brought out of the glovebox.…”
Section: Synthesis Of C 6 Eo 4 π Monomermentioning
confidence: 99%
“…Macrocycles could also be reformed on breaking the hydrogenbonding network in the catenanes by incorporation of (CF 3 CO) 2 O in the presence of catalyst 1. A similar influence of noncovalent interactions in rotaxane [119] and catenane [120] formation was subsequently described by the Grubbs group. Weak perfluorophenyl-phenyl interactions were utilized by Collins and coworkers in the RCM synthesis of paracyclophanes ( Figure 16) [121] The perfluorinated ring present in 20b was proposed to "shield" one side of the cyclophane, orienting both allyl chains in close proximity [122], and enabling RCM in moderate yields (41%).…”
Section: Non-covalent Interactionsmentioning
confidence: 75%
“…It has been shown that both structures III and IV can be utilized successfully in the self-assembly of dynamic [2]rotaxanes [164,178,185,200,[208][209]. The reversibly formed component can be located in either the dumbbell (III) or the ring (IV) components, thus allowing for threading-followed-by-stoppering and clipping approaches, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another important investigation on some interlocked molecular compounds synthesized thermodynamically was recently reported by the Grubbs group [200]. In this work, the well established mutual recognition exhibited by secondary dialkylammonium (R 2 NH 2 + ) ions and suitably sized crown ethers is combined, in an elegant fashion, with the versatile reversible RCM reaction.…”
mentioning
confidence: 98%